2017
DOI: 10.1016/j.jsat.2017.05.010
|View full text |Cite
|
Sign up to set email alerts
|

Very early disengagement and subsequent re-engagement in primary care Office Based Opioid Treatment (OBOT) with buprenorphine

Abstract: Introduction Patients with opioid use disorder often require multiple treatment attempts before achieving stable recovery. Rates of disengagement from buprenorphine are highest in the first month of treatment and termination of buprenorphine therapy results in return to use rates as high as 90%. To better characterize these at-risk patients, this study aims to describe: 1) the frequency and characteristics of patients with very early disengagement (≤1 month) from Office Based Opioid Treatment (OBOT) with bupre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 48 publications
1
15
0
Order By: Relevance
“…In addition, compared with patients with commercial insurance, they were a decade older, had greater access to comprehensive care for substance use disorders, and were likely to have far lower copays (38,39). Higher age, a consistent predictor of better buprenorphine treatment retention (21,(40)(41)(42)(43), may also have contributed to better retention in the VHA. However, in the Massachusetts study that showed high retention (37), the age distribution was similar to that in the study reported here.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, compared with patients with commercial insurance, they were a decade older, had greater access to comprehensive care for substance use disorders, and were likely to have far lower copays (38,39). Higher age, a consistent predictor of better buprenorphine treatment retention (21,(40)(41)(42)(43), may also have contributed to better retention in the VHA. However, in the Massachusetts study that showed high retention (37), the age distribution was similar to that in the study reported here.…”
Section: Discussionmentioning
confidence: 99%
“…In previous research, higher average daily doses of buprenorphine (approximately 16 mg) predicted better treatment retention (Hser et al, 2014; Khemiri, Kharitonova, Zah, Ruby, & Toumi, 2014; Timko et al, 2016), and higher doses received early in treatment were shown to be particularly important for stabilizing and retaining patients (Gryczynski et al, 2014; Timko et al, 2016). Furthermore, higher doses of buprenorphine are associated with lower rates of opioid use during treatment, which is a risk factor for relapse and premature discontinuation (Hser et al, 2014; Hui et al, 2017; Mattick, Breen, Kimber, & Davoli, 2014). A recent study of medical records identified relapse as the most common reason for early discontinuation, particularly among those who discontinued in the first year compared to those with longer treatment (Weinstein et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…We defined buprenorphine treatment discontinuation as >30 days without buprenorphine supply. Previous studies examining buprenorphine treatment episodes used longer, 60-day (Saloner et al, 2017) and 90-day (Hui et al, 2017) definitions of discontinuation. Our goal was to capture discontinuation, rather than gaps in treatment, while also producing results that correspond to the relatively short period after discontinuing treatment in which risk for adverse opioid-related outcomes (e.g.…”
Section: Methodsmentioning
confidence: 99%
“…Discontinuation of treatment can occur for a variety of reasons related to patient (e.g., relapse), provider (e.g., quality of care), and system factors (e.g., arbitrary limits of duration of care). [21][22][23][24][25][26] Research priorities include understanding how to implement chronic disease management for MOUD, understanding factors leading to MOUD discontinuation, and re-engaging patients who discontinue care. 27 Finally, studying interventions to link patients who have a non-fatal overdose to MOUD treatment was deemed a high priority.…”
Section: Managing Opioid Use Disordermentioning
confidence: 99%